Genome Comparison of an Ancestral Isolate and a Modern Isolate of Mycobacterium tuberculosis of the Beijing Lineage from São Paulo, Brazil - Gomes, Lia Lima (2015)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Biologia Molecular Aplicada à Micobactérias. Rio de Janeiro, RJ, Brasil.